Comprensión lectora y rendimiento académico en estudiantes de 5° y 6° grado de primaria del Callao - Gómez Torres, Rebeca Margarita (2010)
We aimed to establish the relationship between levels of reading comprehension and academic performance in the course of Integral Communication (Comunicacion Integral). The sample consisted of 156 participants (81 males and 75 females) from 10 to 11 years old from the 5th and 6th grade, group chosen for convenience, of a Catholic School in Callao. To determine levels of reading comprehension, we used the ACL test, which validity and reliability is (0876) according to the alpha Combrach. The academic performance was obtained from the final average of the course of Integral Communication. The Spearman correlation index is 0.01, a positive correlation between the two variables. However, when analyzing the specific points in the 6th grade test, significant differences were found between the final average and inferential level, p = 0.809> 0.05. & with the level of reorganization and final average, p = 0.223> 0.05. A better understanding of the text will improve academic performance.